Cash Transfers, Trust, and Inter-household Transfers: Experimental Evidence from Tanzania - Evans, David; Kosec, Katrina (International Food Policy Research Institute, 2022)
2022 UPDATE: Institutionalized conditional cash transfer (CCT) programs may affect important as pects of pre-existing, informal safety nets such as inter-household transfers and trust among community members. We use a randomized controlled trial to test the impact of CCTs on various measures of trust and informal safety nets within communities in Tanzania. We find evidence that the introduction of a CCT program increased program beneficiaries’ trust in other community members and their perceived ability to access support from other households (e.g., childcare). Although CCTs reduced the total size of transfers to beneficiary households in the community in the short run (after 1.75 years of transfers), that reduction had disappeared 2.75 years after transfers began. Taken together, our evidence suggests that formal CCT programs do not necessarily crowd out informal safety nets in the longer term, and they may in fact boost trust and support across households.